2022
DOI: 10.21203/rs.3.rs-1192564/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice towards Essential Newborn Care among Postnatal Mothers Attending Health Facilities in a Rural District, Eastern Uganda. A Cross-Sectional Community study

Abstract: Background: Neonatal mortality remains a public health concern in developing countries such as Uganda. Three-quarters of all newborn deaths occur in the first week of life, with 50% occurring during the first 24-hours. The World Health Organization developed essential newborn care measures to improve neonatal outcomes.This study aimed at determining maternal knowledge attitude and practices towards essential newborn care in Mbale district, Eastern Uganda.Methods: A hospital-based cross-sectional survey employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…This contrary might be due to differences in educational systems across countries. In the same context, this result aligned with the study [10], which reported that the Participants' mean age was 26.13±5.69; the majority of the mothers were aged between 20-29 years; the majority were married. and around two third of them were unemployed.…”
Section: Discussionsupporting
confidence: 86%
“…This contrary might be due to differences in educational systems across countries. In the same context, this result aligned with the study [10], which reported that the Participants' mean age was 26.13±5.69; the majority of the mothers were aged between 20-29 years; the majority were married. and around two third of them were unemployed.…”
Section: Discussionsupporting
confidence: 86%